Initial value & Final value Theorems in Z-Transforms:-

Initial  value Theorem (Z-Transforms):-

If uni-lateral Z-Transform of x[n] is X_{+}(Z)  then  x(0) = \lim_{z\rightarrow \infty } X_{+}(Z) .

X_{+}(Z) = \sum_{n=0}^{\infty } x[n] \ Z^{-n} .

X_{+}(Z) = x(0) +x(1)\ Z^{-1}+ x(2)\ Z^{-2}+x(3)\ Z^{-3}+......

\lim_{Z\rightarrow \infty }X_{+}(Z) = \lim_{Z\rightarrow \infty }\left

\lim_{Z\rightarrow \infty }X_{+}(Z) = x(0) .

Final  value Theorem (Z-Transforms):-

If uni-lateral Z-Transform of x[n] is X_{+}(Z)  then  x(\infty ) = \lim_{z\rightarrow 1}(Z-1) \ X_{+}(Z) .

Z\left \{ x(n+1) \right \}-Z\left \{ x(n) \right \} = \lim_{k\rightarrow \infty }\sum_{n=0}^{k} (x[n+1]-x[n]) \ Z^{-n} .

Z\ X_{+}(Z) -x(0)-X_{+}(Z)= \lim_{k\rightarrow \infty }\sum_{n=0}^{k} (x[n+1]-x[n]) \ Z^{-n}.

\lim_{z\rightarrow 1}\left =\lim_{z\rightarrow 1} \lim_{k\rightarrow \infty }\sum_{n=0}^{k} \left

\lim_{z\rightarrow 1}\left = \lim_{z\rightarrow 1}\left \{ x(\infty )-x(0) \right \}.

\lim_{z\rightarrow 1}(Z-1)\ X_{+}(Z) = x(\infty ).

Note: There is a rating embedded within this post, please visit this post to rate it.

Author: Lakshmi Prasanna Ponnala

Completed M.Tech in Digital Electronics and Communication Systems.

Leave a Reply

Insert math as
Block
Inline
Additional settings
Formula color
Text color
#333333
Type math using LaTeX
Preview
\({}\)
Nothing to preview
Insert
%d bloggers like this: